ORAL AND MAXILLOFACIAL NON-HODGKIN'S LYMPHOMAS - Andrei Nicolau; Daniela Sulea; Alexandra Cracana; Raluca Andrada Doscas; Mihai Liviu Ciofu (Romanian Society of Oral Rehabilitation, 2018)
Aim of the study is to assess the clinical-epidemiological and morphological features of the lymphomas located in the oral and maxillofacial territory, including the research of histopathological forms involved and anatomical sites affected. It has also been analyzed their progress and response to treatment, as well as the patients` rate of survival. Material and methods The study has been conducted within the Department of Oral and Maxillofacial Surgery - "Sf. Spiridon" Iasi for a period of 7 years (from 2010 to 2017), analyzing the data recorded in 70 patients diagnosed with oral and maxillofacial non-Hodgkin's lymphomas. Results Oral and maxillofacial Non-Hodgkin's lymphomas are most often diagnosed in elder people, in advanced stages (42% of the cases in stage IV). The extranodal presentation occurs in 55% of the patients, the parotid gland being the most frequent site. Conclusions Diffuse Large B-cell Lymphoma is the most common subtype. Chemotherapy is the most used therapeutic method in a multimodal treatment and the survival rate is 58%, with better results when the treatment is applied in the early stages.